Stable isotopes reveal trophic segregation by sex and age in the southern giant petrel in two different food webs - Forero, Manuela G.; González-Solís, Jacob; Hobson, Keith A.; Donázar, José A.; Bertellotti, Néstor Marcelo; Blanco, Guillermo; Bortolotti, Gary R. (Marine Ecology Progress Series)
We investigated trophic ecology variation among colonies as well as sex- and age-related differences in the diet of the southern giant petrel Macronectes giganteus, a long-lived seabird that is sexually dimorphic in size. We measured stable isotopes (δ13C, δ15N) in blood samples collected during breeding at Bird Island (South Georgia, Antarctica) in 1998 and at 2 colonies in the Argentinean area of Patagonia in 2000 and 2001. Individuals from South Georgia showed lower δ13C and δ15N values than those in Patagonia, as expected from the more pelagic location and the short length of the Antarctic food web. Males and females showed significant differences in the isotopic signatures at both localities. These differences agree with the sexual differences in diet found in previous studies, which showed that both sexes rely mainly on penguin and seal carrion, but females also feed extensively on marine prey, such as fish, squid and crustaceans. However, males from Patagonia showed significantly higher δ15N andδ13C values than females did, and the reverse trend was observed at South Georgia. This opposite trend is probably related to the different trophic level of carrion between locations: whereas penguins and pinnipeds in Patagonia rely mainly on fish and cephalopods, in South Georgia they rely mainly on krill. Stable isotope values of male and female chicks in Patagonia did not differ; both attained high values, similar to adult males and higher than adult females, suggesting that parents do not provision their single offspring differently in relation to sex; however, they seem to provide offspring with a higher proportion of carrion, probably of higher quality, and more abundant food, than they consume themselves. Stable isotopes at South Georgia were not affected by age of adults. We have provided new information on intraspecific segregation in the diet in a seabird species and have also underlined the importance of considering food web structure when studying intraspecific variability in trophic ecology. Fil: ...